2004
DOI: 10.1021/es034149x
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of Methyl Iodide in Aqueous Solution and Soils Amended with Thiourea

Abstract: Methyl iodide (MeI) is considered a very promising fumigant alternative to methyl bromide (MeBr) for controlling soil-borne pests. Because atmospheric emission of highly volatile fumigants contributes to air pollution, feasible strategies to reduce emissions are urgently needed. In this study, thiourea (a nitrification inhibitor) was shown to accelerate the degradation of MeI in soil and water. In aqueous solution, the reaction between MeI and thiourea was independent of pH, although the rate of MeI hydrolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 37 publications
1
22
1
Order By: Relevance
“…These authors concluded that half-lives were not drastically affected by soil sterilization. The same conclusion was drawn by Zheng et al (2004), suggesting that MeI is degraded primarily by chemical, rather than biological, processes. Such processes may be facilitated by the presence of soil organic matter and, more specifically, the fumigant-degrading nature of functional groups present in the molecular structure of the organic matter.…”
Section: Transformation In Soilsupporting
confidence: 68%
See 4 more Smart Citations
“…These authors concluded that half-lives were not drastically affected by soil sterilization. The same conclusion was drawn by Zheng et al (2004), suggesting that MeI is degraded primarily by chemical, rather than biological, processes. Such processes may be facilitated by the presence of soil organic matter and, more specifically, the fumigant-degrading nature of functional groups present in the molecular structure of the organic matter.…”
Section: Transformation In Soilsupporting
confidence: 68%
“…The authors propose that in aqueous solutions of these chemicals, (C 2 H 5 ) 2 NSCS  exists as the strongly nucleophilic thiolate ion, which is susceptible to SN 2 nucleophilic substitution reactions with halogenated hydrocarbons, e.g. : Zheng et al (2004) studied the effect of thiourea (a nitrification inhibitor) on MeI transformation in aqueous solution at various pH values. These authors found that both in the presence and absence of thiourea, neutral and base-catalyzed hydrolysis of MeI significantly decreased the half-life of the fumigant as pH increased above circum-neutrality (from 381 h at pH 6.9 to 106 h at pH 12).…”
Section: Transformation In Aqueous Solutionmentioning
confidence: 99%
See 3 more Smart Citations